The Traders’ Cave of Niah (NW Borneo): morphology and features as indicators of speleogenesis and karstification - Dodge-Wan, Dominique (Springer, 2017)
© 2017 Springer-Verlag GmbH Germany Relict caves which are isolated from regional groundwater flow are common in deeply dissected tropical tower karsts. Their passage morphology and the micro-morphology of their walls can provide valuable information on former karst processes and speleogenesis. The Traders’ Cave at Niah (Sarawak, Malaysia) was selected for a case study including comprehensive survey and observations to establish a model of the cave’s formation which can serve as a basis for comparison with other caves in the region. The research identified six levels of vadose alluvial notches showing evidence of relative water-level drop of at least 15 m during the main vadose phase of speleogenesis. During this phase, the passage reached its maximal dimensions, possibly over 90 m wide. The notches are associated with paragenetic ceiling anastomoses formed by upward or antigravitative erosion. The results indicate that point-recharge allogenic flow, i.e., sinking streams from non-karst terrains, and sediment transport and removal played a major role during cave formation. The position of limestone boulders within the cave suggests that cave-ceiling collapse and un-roofing contributed to erosion of a large part of the cave and formation of the steep-sided valley between adjacent karst towers. The collapse is linked to landscape rejuvenation associated with a significant relative water-level drop leading to the present situation in which the Traders’ Cave is isolated and relict. Most speleothems post-date the opening of the cave into the karst valley and are fed by epikarstic flow. Many speleothems are phototropic, indicating a biological influence.